Subspace-Based Algorithms for Structural Identification, Damage Detection, and Sensor Data Fusion. (16th October 2006) - Basseville Basseville, Michèle Michèle; Benveniste Benveniste, Albert Albert; Goursat Goursat, Maurice Maurice; Mevel Mevel, Laurent Laurent
Abstract : This paper reports on the theory and practice of covariance-driven output-only and input/output subspace-based identification and detection algorithms. The motivating and investigated application domain is vibration-based structural analysis and health monitoring of mechanical, civil, and aeronautic structures.